2016
DOI: 10.1038/srep18787
|View full text |Cite
|
Sign up to set email alerts
|

The nature of Ordovician limestone-marl alternations in the Oslo-Asker District (Norway): witnesses of primary glacio-eustasy or diagenetic rhythms?

Abstract: Ordovician limestone-marl alternations in the Oslo-Asker District have been interpreted as signaling glacio-eustatic lowstands, which would support a prolonged “Early Palaeozoic Icehouse”. However, these rhythmites could alternatively reflect differential diagenesis, without sedimentary trigger. Here, we test both hypotheses through one Darriwilian and three Katian sections. Our methodology consists of a bed-by-bed analysis of palynological (chitinozoan) and geochemical (XRF) data, to evaluate whether the lime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…It is also still unclear how glacial onset could have possibly occurred in the midst of a prolonged period of hot climate. Evidence for warm shallow seas in the tropics (up to 37°C) [ Finnegan et al , ], as suggested by most recent Ordovician geochemical data [ Trotter et al , ; Finnegan et al , ], is in apparent contradiction with Middle to Upper Ordovician deposits where glacioeustatic events are identified [ Loi et al , ; Turner et al , ; Elrick et al , ; Dabard et al , ; Rasmussen et al , ] or suggested [ Nielsen , ] (see discussion in Amberg et al []). These eustatic cycles support the presence of ice sheets since the Middle Ordovician Darriwilian (467 Ma) rather than a sudden emplacement of a massive ice sheet restricted to the Hirnantian stage (445–444 Ma).…”
Section: Introductionmentioning
confidence: 99%
“…It is also still unclear how glacial onset could have possibly occurred in the midst of a prolonged period of hot climate. Evidence for warm shallow seas in the tropics (up to 37°C) [ Finnegan et al , ], as suggested by most recent Ordovician geochemical data [ Trotter et al , ; Finnegan et al , ], is in apparent contradiction with Middle to Upper Ordovician deposits where glacioeustatic events are identified [ Loi et al , ; Turner et al , ; Elrick et al , ; Dabard et al , ; Rasmussen et al , ] or suggested [ Nielsen , ] (see discussion in Amberg et al []). These eustatic cycles support the presence of ice sheets since the Middle Ordovician Darriwilian (467 Ma) rather than a sudden emplacement of a massive ice sheet restricted to the Hirnantian stage (445–444 Ma).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these two well‐documented observations, it follows that a constant element ratio will be also retained across a succession where aragonite or calcite input in the precursor sediment varied. This theoretical prediction has been corroborated empirically (Westphal e t al ., 2008, 2010; Amberg et al ., 2016).…”
Section: Novel Approach To Identifying Variations In Aragonite and Ca...mentioning
confidence: 99%
“…Les plaques d'échinodermes observées au sein du faciès sont peu usées, et probablement exotiques, apportées sous forme d'éléments flottés. L'effet de la diagenèse précoce dans le développement des alternances rythmiques à partir de sédiments préalablement homogènes a été démontrée par certains auteurs (MUNNECKE, 1997 ;MUNNECKE & SAMTLEBEN, 1996 ;WESTPHAL & MUNNECKE, 2003 ;RIDING & LIANG, 2005 ;WESTPHAL, 2006 ;AMBERG et al, 2016), distinguant un flux des eaux interstitielles soit dirigé vers le bas (cf. JENKYNS, 1974), soit entraîné et dirigé vers le haut par compactage (cf.…”
Section: Faciès De Plateforme Carbonatée Distale (unclassified